Risk of Postdural Puncture Headache in Adolescents and Adults. (July 2020) - DelPizzo, Kate; Luu, Thuyvan; Fields, Kara G.; Sideris, Alexandra; Dong, Naomi; Edmonds, Chris; Zayas, Victor M.
Abstract : BACKGROUND: Spinal anesthesia is known to have numerous benefits, including reductions in nausea and opioid consumption; however, postdural puncture headache (PDPH) remains a significant risk associated with this technique. The literature specifically examining this complication in adolescents is scarce. Our primary objective was therefore (1) to estimate the incidence of PDPH with a 27G pencil-point needle in patients between the ages of 12 and 19 undergoing ambulatory lower extremity procedures and (2) to compare it to the incidence in adults aged 20–45 years. METHODS: After institutional review board (IRB) approval, patients aged 12–45 years undergoing ambulatory lower extremity surgery were approached. Patients undergoing the procedure under combined spinal-epidural (CSE) or spinal anesthesia with a 27G pencil-point needle were eligible for enrollment. Patients were consented before surgery and received a survey via e-mail on postoperative day (POD) 4 inquiring about the presence of a headache. Each headache was described by the participant and assessed for severity, time of onset, duration, location, and whether it was of a postural nature. All patients reporting a postural headache were contacted by a physician author to confirm a diagnosis of PDPH using the International Headache Society diagnostic criteria. RESULTS: A total of 656 patients were included in the analysis. Overall, 3.4% of patients developed PDPH. The percentage developing PDPH was 4.9% (3.0–7.8) among those aged 12–19 years and 1.8% (0.8–3.9) in the 20- to 45-year-old group. After adjusting for covariates, the age group between 12 and 19 years was associated with an almost 3-fold increase in the odds (2.8 [95% confidence interval CI, 1.1–7.3]) for the development of PDPH compared to that in the 20–45 age group. One patient in the adult group required an epidural blood patch. CONCLUSIONS: The overall incidence for the development of PDPH in ambulatory patients <45 years of age is low. However, the odds for developing PDPH is significantly higher in teenagers compared to those aged 20–45 years. This increase was not associated with an increase in the need for an epidural blood patch. Providers may incorporate these data in their consent process and have a higher index of suspicion for PDPH in teenagers who report headaches after neuraxial anesthesia.